2019
DOI: 10.1016/j.cbpa.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration during egg production alters egg composition and yolk immune function

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Previous work has shown that environmental characteristics, including climate, pathogen intensity, resource abundance, and pollution can impact indices of innate immunity (Bowden, 2008; Brusch et al., 2019; Georgiev et al., 2016; McDade et al., 2016; Vermeulen et al., 2015). Consequently, we predicted that annual climatic variation associated with drought, which has already been shown to decrease body condition and reproductive success in reptiles, would result in a decrease in innate immunity in garter snakes (Allen et al., 2010; Capehart et al., 2016; Urban, 2015; Zani & Stein, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work has shown that environmental characteristics, including climate, pathogen intensity, resource abundance, and pollution can impact indices of innate immunity (Bowden, 2008; Brusch et al., 2019; Georgiev et al., 2016; McDade et al., 2016; Vermeulen et al., 2015). Consequently, we predicted that annual climatic variation associated with drought, which has already been shown to decrease body condition and reproductive success in reptiles, would result in a decrease in innate immunity in garter snakes (Allen et al., 2010; Capehart et al., 2016; Urban, 2015; Zani & Stein, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The field of eco‐immunology provides a useful framework with which to study physiological reactions to environmental change in free‐living populations (Downs & Stewart, 2014; Martin et al., 2010; Rohr et al., 2013). Immune function is energetically costly to develop and maintain and can shift in response to resource scarcity, water availability, pathogen exposure, and pollution (see Bowden, 2008; Brusch et al., 2019; Georgiev et al., 2016; Lifjeld et al., 2002; Lochmiller & Deerenberg, 2000; McDade et al., 2016; Vermeulen et al., 2015). In particular, innate or nonspecific immunity—the branch of the immune system which is composed of generalist, preexisting mechanisms of defense—may be a particularly useful indicator of population response to chronic environmental stressors since it is (a) not dependent on specific antigens or current infection and (b) can be compared across periods of time or between different environments (Beutler, 2004; Buehler et al., 2008, 2009; Matson et al., 2005; Riera Romo et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bowden, Ewert, & Nelson, ; Parolini, Romano, Caprioli, Rubolini, & Saino, ; Ruuskanen & Hsu, ). In addition, seasonal shifts in water availability to mothers could impact the hydration (and mass) of eggs at oviposition (Brusch, Heulin, & DeNardo, ), which might explain our observed seasonal changes in egg quality (i.e. consistent yolk provisioning, but more water allocation later in the season).…”
Section: Discussionmentioning
confidence: 95%